2008
DOI: 10.1007/s11746-008-1208-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Natural and Synthetic Antioxidants on the Oxidative Stability of Biodiesel

Abstract: A significant problem associated with the commercial acceptance of biodiesel is poor oxidative stability. This study investigates the effectiveness of various natural and synthetic antioxidants [a-tocopherol (a-T), butylated hydroxyanisole (BHA), butyl-4-methylphenol (BHT), tert-butylhydroquinone (TBHQ), 2, 5-di-tert-butylhydroquinone (DTBHQ), ionol BF200 (IB), propylgallate (PG), and pyrogallol (PY)] to improve the oxidative stability of soybean oil (SBO-), cottonseed oil (CSO-), poultry fat (PF-), and yellow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(97 citation statements)
references
References 23 publications
7
76
0
8
Order By: Relevance
“…Oxidative degradation during storage can also compromise fuel quality with respect to effects on kinematic viscosity, acid value, cetane number, total ester content, and formation of hydroperoxides, soluble polymers, and other secondary products (Du Plessis et al, 1985;Bondioli et al, 2002;Thompson et al, 1998). The increased acidity and peroxide values as a result of oxidation reactions can also cause the corrosion of fuel system components, the hardening of rubber components and the erosion of moving parts (Tang et al, 2008). By now the only method for increasing the biodiesel resistance to oxidation is to add synthetic or natural oxidation inhibitors such as tocopherols and hydroquinones.…”
Section: The Needs For Refining Of Petrodiesel and Biodiesel Fuelsmentioning
confidence: 99%
“…Oxidative degradation during storage can also compromise fuel quality with respect to effects on kinematic viscosity, acid value, cetane number, total ester content, and formation of hydroperoxides, soluble polymers, and other secondary products (Du Plessis et al, 1985;Bondioli et al, 2002;Thompson et al, 1998). The increased acidity and peroxide values as a result of oxidation reactions can also cause the corrosion of fuel system components, the hardening of rubber components and the erosion of moving parts (Tang et al, 2008). By now the only method for increasing the biodiesel resistance to oxidation is to add synthetic or natural oxidation inhibitors such as tocopherols and hydroquinones.…”
Section: The Needs For Refining Of Petrodiesel and Biodiesel Fuelsmentioning
confidence: 99%
“…It was found that the cooperated antioxidants performed better than single one. 13 Tang et al 14 found that pyrogallol (PY), propylgallate (PG) and TBHQ can significantly improve the IP of soybean oil, cotton seed oil, poultry fat and yellow grease based biodiesels, while PY, BHA and BHT showed the best results for poultry fat based biodiesel. Mittelbach and Schober 15 reported that the stability of biodiesels derived from apeseed oil, used frying oil, and tallow was considerably improved with PY, PG, and TBHQ additions, whereas antioxidant BHT was not very effective.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stability of biodiesel was improved by adding natural and synthetic antioxidants at the varying concentrations between 250 and 1000 ppm [31][32][33]. The various natural and synthetic antioxidants [α-tocopherol (α-T), butylated hydroxyanisole (BHA), butyl-4-methylphenol (BHT), tert-butylhydroquinone (TBHQ), 2, 5-di-tert-butyl-hydroquinone (DTBHQ), ionol BF200 (IB), propylgallate (PG), and pyrogallol (PY)] improve the oxidative stability of soybean oil (SBO), cottonseed oil (CSO), poultry fat (PF), and yellow grease (YG) based biodiesel.…”
Section: Effect Chemical Additives On Oxidation Stabilitymentioning
confidence: 99%